2003
DOI: 10.1177/0273475303254004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Learning Outcomes: The Effects of Instructional Technology, Learning Styles, Instructional Methods, and Student Behavior

Abstract: The delivery of marketing education seems to be rapidly shifting toward pedagogy rich in experiential learning and strongly supported with educational technology. This study integrates and extends previous research efforts and investigates the simultaneous effects of multiple influences of technology and nontechnology factors on learning outcomes. Responses were obtained across a marketing curriculum with technology-accustomed students. The findings suggest that the use of preferred instructional methods will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
119
0
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(133 citation statements)
references
References 42 publications
2
119
0
12
Order By: Relevance
“…Also, the teacher's role is facilitated (Abrantes, Seabra&Lages, 2007;Young, Klemz& Murphy 2003). Students reject learning environments that they don't like and, moreover, their perception of learning is worse in those environments (Hsu, 1999).…”
Section: Personal Factors and Learning Stylesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the teacher's role is facilitated (Abrantes, Seabra&Lages, 2007;Young, Klemz& Murphy 2003). Students reject learning environments that they don't like and, moreover, their perception of learning is worse in those environments (Hsu, 1999).…”
Section: Personal Factors and Learning Stylesmentioning
confidence: 99%
“…Students reject learning environments that they don't like and, moreover, their perception of learning is worse in those environments (Hsu, 1999). In this context, student's intrinsic factors, the learning environment and styles are important issues to examine how students focus on the contents (Young et al, 2003;Hamer, 2000;Clarke III, Flaherty &Mottner, 2001). The theory of learning styles points to individual preference-related factors, such as: environment, emotions, interactions and physical needs that have an impact on the learning process (Dunn & Griggs, 1995).…”
Section: Personal Factors and Learning Stylesmentioning
confidence: 99%
“…This can be achieved through cooperative educational activities, wherein students are divided into small electronic discussion groups to achieve common educational goals . [5] As the digital tools and multimedia promote individualized instruction, these can be employed to give students experience in a subjective manner on their own, with the teacher designing lessons centered on the student's individual characteristics using programmed learning such as modeling, simulation and role-playing games in extra-curricular educational activities [6]. The lessons are delivered by a qualified teacher using modern technological applications (a PowerPoint presentation, for example).…”
Section: A Assure Modelmentioning
confidence: 99%
“…Recently, much marketing education research has concentrated on how to enhance students' learning outcomes in the marketing discipline (e.g., Duke, 2002;Sautter, 2007;Young, Klemz, & Murphy, 2003). Several studies have suggested that students' learning outcomes are related to their learning styles (Bliuc et al, 2010;Young et al, 2003;Zeegers, 2001).…”
Section: Business and Economic Researchmentioning
confidence: 99%
“…Several studies have suggested that students' learning outcomes are related to their learning styles (Bliuc et al, 2010;Young et al, 2003;Zeegers, 2001). For example, Zeegers (2001) has illustrated that the deep approach shows a consistent positive correlation with assessment outcomes.…”
Section: Business and Economic Researchmentioning
confidence: 99%